2020
DOI: 10.15407/bioorganica2020.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the extract's composition of Viper's bugloss (Echium vulgare)

Abstract: The characteristics of Viper's bugloss (Echium vulgare) plant, its pharmacological properties, and extracts’ composition are presented in this study. Results of the literature analysis, data on the biologically active compounds and areas of use of this medicinal plant are summarized. Viper's bugloss (E. vulgare) is a species of flowering plant in the borage family Boraginaceae. It is native to most of Europe as well as western and central Asia. Viper's bugloss (E. vulgare) is a plant that has been utilized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to the relative abundance of the fragment ions and their retention times, they were identified as 3-and 5-caffeoylquinic acids. In addition, one dicaffeoylquinic acid isomer was also detected with a deprotonated molecular [2] C, [6,7] EV, [24,25] EI, [7,26] O [27] A, [28] EV [29] PA3 Caffeic acid 12.5 226, 298sh, 328 179 135 C, EV A, [2] EV, [24] EI, [26] O [27 [2] C, [6] EI, [26] O [27 A [2] , C [6,7] , EV [24,25] , EI [7,26] , O [27] [2] C, [6] EI, [26] ion at m/z 515 and product ions at m/z 353 (loss of caffeoyl moiety) and at m/z 173 (quinic acid-H 2 O).…”
Section: Characterization and Distribution Of Phenolic Compoundsmentioning
confidence: 99%
“…According to the relative abundance of the fragment ions and their retention times, they were identified as 3-and 5-caffeoylquinic acids. In addition, one dicaffeoylquinic acid isomer was also detected with a deprotonated molecular [2] C, [6,7] EV, [24,25] EI, [7,26] O [27] A, [28] EV [29] PA3 Caffeic acid 12.5 226, 298sh, 328 179 135 C, EV A, [2] EV, [24] EI, [26] O [27 [2] C, [6] EI, [26] O [27 A [2] , C [6,7] , EV [24,25] , EI [7,26] , O [27] [2] C, [6] EI, [26] ion at m/z 515 and product ions at m/z 353 (loss of caffeoyl moiety) and at m/z 173 (quinic acid-H 2 O).…”
Section: Characterization and Distribution Of Phenolic Compoundsmentioning
confidence: 99%
“…Results showed that the total flavonoid concentration in the extract was 2.59% and the maximum yield obtained from this extraction procedure was 16% (Kapusterynska et al, 2020). Antioxidant properties of the methanol based extract of E. vulgare were investigated by DPPH methodology, focusing on phenolic and flavonoid components.…”
Section: Mcf7 Cell Linementioning
confidence: 99%
“…The perennial herb Echium vulgare is a member of the Boraginaceae family's Echium genus. It performs best when growing naturally in areas with plenty of sunlight, fields, overgrazing pastures, poor draining valleys, and roadside locations (Kapusterynska et al, 2020). Echium species exhibit various life cycles as annual, biennial or perennial in their natural habitats and are known for their beautiful flowering appearance (Jin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%